2018
DOI: 10.1007/s11418-018-1178-x
|View full text |Cite
|
Sign up to set email alerts
|

Terpenoids from Vitex trifolia and their anti-inflammatory activities

Abstract: A new diterpenoid glucoside, (3S,5S,6S,8R,9R,10S)-3,6,9-trihydroxy-13(14)-labdean-16,15-olide 3-O-β-D-glucopyranoside (1), and a new iridoid glucoside, (1S, 5S,6R,9R)-10-O-p-hydroxybenzoyl-5,6β-dihydroxy iridoid 1-O-β-D-glucopyranoside (2), along with six known compounds (3-8) were isolated from Vitex trifolia L.. Their structures were elucidated by extensive spectroscopic analysis. All these isolated compounds were evaluated for their inhibitory effects on nitric oxide production in LPS-induced RAW 264.7 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Furthermore, a new iridoid glycoside was found in V . trifolia L. producing (1 S , 5 S ,6 R ,9 R )-10- O - p -hydroxybenzoyl-5,6 β -dihydroxy iridoid 1- O - β -D-glucopyranosidem ( 22 ) [ 82 ]. The isolated compound 22 was assessed for NO inhibitory activity tested on LPS-induced murine macrophage (RAW 264.7) cells to exhibit moderate inhibitory activity with an IC 50 value of 90.05 μM.…”
Section: Secondary Metabolites Isolated From Vitex ...mentioning
confidence: 99%
“…Furthermore, a new iridoid glycoside was found in V . trifolia L. producing (1 S , 5 S ,6 R ,9 R )-10- O - p -hydroxybenzoyl-5,6 β -dihydroxy iridoid 1- O - β -D-glucopyranosidem ( 22 ) [ 82 ]. The isolated compound 22 was assessed for NO inhibitory activity tested on LPS-induced murine macrophage (RAW 264.7) cells to exhibit moderate inhibitory activity with an IC 50 value of 90.05 μM.…”
Section: Secondary Metabolites Isolated From Vitex ...mentioning
confidence: 99%
“…Based on this, developing environmentally friendly incense organic raw materials such as Legundi leaf (Vitex trifolia L.), lemongrass leaves (Andropogon nardus), and wood grain packaged in Legiayu incense, are necessary The pharmacologically content of oleum citronellal, geraniol, tannin, flavonoids, saponins, champine, pinine and polyphenols that serve as insecticides and larvicide (Bao et al, 2018;Chan et al, 2016). These compound has benefits as contact, stomach and respiratory toxins that result in death (Susilowati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoid and tannin are able to provide toxic effects that are able to clump the protein of Aedes aegypti larvae. Flavonoid compounds are able to regulate proteins that result in the permeability of the cell walls of larvae decreased which has an impact on the loss of excitatory stimulus of eating and larvae experience death (Bao et al, 2018;Siew et al, 2019).…”
mentioning
confidence: 99%
“…In Japan, VTF has been taken as a natural analgesic (Oshima et al, 2016). Moreover, recent research has indicated the extensive biological activities of VTF including antitumor (Cao et al, 2016; Haïdara, Zamir, Shi, & Batist, 2006; Kobayakawa, Satonishimori, Moriyasu, & Matsukawa, 2004), antinociceptive, antihyperprolactinemia (Hu et al, 2007), antifibrosis (Zhou et al, 2017), antiinflammation (Bao et al, 2018; Lee, Jung, Ji, & Bae, 2017), antiasthma (Park et al, 2014) as well as the rosiglitazone‐like effects (Nishina et al, 2017). However, the mixing and misuse of other species with VTF were found during the formulation and application, including two congeneric species of VTF namely Vitex cannabifolia fruit (VCF) and Vitex negundo fruit (VNF) (Zhang et al, 2019) along with three adulterant species including Piper cubeba fruit (PCF) (Fam.…”
Section: Introductionmentioning
confidence: 99%